Inversion upstream of FOXF1 in a case of lethal alveolar capillary dysplasia with misalignment of pulmonary veins12. Issue 4 (26th February 2013) - Parris, Toshima; Nik, Ali Moussavi; Kotecha, Sailesh; Langston, Claire; Helou, Khalil; Platt, Craig; Carlsson, Peter
Abstract Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a congenital malformation that leads to severe pulmonary hypertension and respiratory failure. It has been associated with deletion of, or mutation in, FOXF1 on 16q24.1, a gene encoding a forkhead transcription factor expressed in the mesenchyme of the developing lung. Here we report on the identification of a pericentric inversion on chromosome 16 (p11.2q24.1) in a case of lethal ACDMPV with atrioventricular septal defect and duodenal atresia. Array‐CGH indicated that the inversion is balanced, and FISH showed that the q‐arm breakpoint occurs 134 ± 10 kb upstream (5′; centromeric) of FOXF1. This is suggestive of cis‐regulatory elements located more than 130 kb 5′ of FOXF1, and analysis of genome‐wide data sets of chromatin modifications in two different cell types suggested that the FOXF1 regulatory domain covers more than 300 kb, and perhaps up to 433 kb, upstream of the gene, but only 3 kb downstream. The 588 kb gene‐free region between FOXF1 and the next gene in the centromeric direction, IRF8, is highly conserved between species and divided into two distinct regulatory domains by an insulator element. Another putative insulator occurs just downstream of FOXF1. Our results further strengthen the association between FOXF1 and a spectrum of malformations that include ACDMPV, atrioventricular septal defects, and gastrointestinal atresia. Furthermore, the presented analysis aids in defining the critical genomic region for this syndrome. © 2013 Wiley Periodicals, Inc.